Intimate and Personal Sphere in the System of Vital Values of the Anomalous Person – the Offender (Law and Safety, 2019)
The study of the peculiarities of the structural and dynamic characteristics of the value and content sphere of the anomalous personality remains within the scope of actual psychological problems. The purpose of this study is to analyze the peculiarities of value orientations that represent the intimate and personal sphere, in the ideal representation, within conscious and unconscious aspects, as well as to analyze the place of the intimate and personal sphere in the structure of the assessment of reality in persons with specific personality disorders, who committed illegal actions.The authors have studied 100 individuals with personality abnormalities and unlawful behavior. The control group consisted of 50 individuals without personality abnormalities who did not commit offenses and would refer to the main group according to socio-demographic indicators. To obtain results that reflect the system of attitudes of studied individuals to leading values in their own assessment factors, reflecting the leading bases of classification of the validity of these individuals, the authors used J. Kelly’s Test Repertoire of Role Constructs. Subjects’ perceptions of the ideal hierarchy of terminal values were researched using the rank grid as a variant of J. Kelly’s Test Repertoire. To evaluate the systems of conscious values, the authors used E. B. Fantalova’s technique of “Correlation of “value” and “accessibility” in different spheres of life”. Unconscious aspects of attitudes towards these values were studied using the Color Test of the Attitudes of A. M. Etkind. Rank structures were obtained which allowed to distinguish the comparative features of the ideal, conscious and unconscious aspects of the attitude towards values of intimate and personal relations of anomalous persons in comparison with the control group.The data obtained demonstrated that the system of attitude towards the values of the intimate and personal sphere in the control group, was more harmonious and formed than in the main group, with an overall high assessment of the values of the intimate and personal orientation. It is demonstrated that defined structural and dynamic characteristics of the value sphere of anomalous individuals indirectly determine personal disharmony. These differences are at the root of the motivational and contentious conflict associated with the intimate and personal relationships of the anomalous individuals. This internal conflict of psychopathic personality causes the failure of its self-realization in this sphere of vital activity. It is emphasized that psycho-corrective work with anomalous personalities should be directed to harmonization, increase of structure and awareness of their own system of value orientations, in particular values, which represent the intimate and personal sphere.
Keywords: specific personality disorders; value orientations; attitude; intimate and personal relationships; happy family life; love; existence of friends; content-related formations